2019
DOI: 10.3389/fnagi.2019.00064
|View full text |Cite
|
Sign up to set email alerts
|

Affibody-Mediated Sequestration of Amyloid β Demonstrates Preventive Efficacy in a Transgenic Alzheimer’s Disease Mouse Model

Abstract: Different strategies for treatment and prevention of Alzheimer’s disease (AD) are currently under investigation, including passive immunization with anti-amyloid β (anti-Aβ) monoclonal antibodies (mAbs). Here, we investigate the therapeutic potential of a novel type of Aβ-targeting agent based on an affibody molecule with fundamentally different properties to mAbs. We generated a therapeutic candidate, denoted Z SYM73 -albumin-binding domain (ABD; 16.8 kDa), by genetic linkage of the dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 56 publications
1
28
0
Order By: Relevance
“…The CSF bioavailability of the control protein Z SYM73 -ABD was 0.12%, 0.16%, and 0.29% at 3 h, 24 h, and 48 h, respectively ( Figure 4E). The CSF bioavailability of Z SYM73 -ABD is in accordance with a recent study carried out in rats [27] and reflects values reported for passive protein uptake into the CNS [43]. The fusion of scFv8D3 to Z SYM73 -ABD led to an 9-fold increase in CSF bioavailability after 24 h indicating an active transport mechanism into CSF.…”
Section: Bioavailability Of the Affibody Fusion Proteins In Mouse Csfsupporting
confidence: 89%
See 4 more Smart Citations
“…The CSF bioavailability of the control protein Z SYM73 -ABD was 0.12%, 0.16%, and 0.29% at 3 h, 24 h, and 48 h, respectively ( Figure 4E). The CSF bioavailability of Z SYM73 -ABD is in accordance with a recent study carried out in rats [27] and reflects values reported for passive protein uptake into the CNS [43]. The fusion of scFv8D3 to Z SYM73 -ABD led to an 9-fold increase in CSF bioavailability after 24 h indicating an active transport mechanism into CSF.…”
Section: Bioavailability Of the Affibody Fusion Proteins In Mouse Csfsupporting
confidence: 89%
“…In this study, we investigated CSF bioavailability of affibody fusion proteins after administrating a therapeutically relevant dose of 87.8 nmol/kg. These doses are comparable to doses administered in a preclinical study of Z SYM73 -ABD and significantly larger than doses used in previous studies exploiting TfR brain uptake using the 8D3 antibody [27,28,44].…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations